Contribution of indirect effects to clustered damage in DNA irradiated with protons - Pachnerová Brabcová, K; Štěpán, V; Karamitros, M; Karabín, M; Dostálek, P; Incerti, S; Davídková, M; Sihver, L (Radiation protection dosimetry, 2015)
Protons are the dominant particles both in galactic cosmic rays and in solar particle events and, furthermore, proton irradiation becomes increasingly used in tumour treatment. It is believed that complex DNA damage is the determining factor for the consequent cellular response to radiation. DNA plasmid pBR322 was irradiated at U120-M cyclotron with 30 MeV protons and treated with two Escherichia coli base excision repair enzymes. The yields of SSBs and DSBs were analysed using agarose gel electrophoresis. DNA has been irradiated in the presence of hydroxyl radical scavenger (coumarin-3-carboxylic acid) in order to distinguish between direct and indirect damage of the biological target. Pure scavenger solution was used as a probe for measurement of induced OH· radical yields. Experimental OH· radical yield kinetics was compared with predictions computed by two theoretical models-RADAMOL and Geant4-DNA. Both approaches use Geant4-DNA for description of physical stages of radiation action, and then each of them applies a distinct model for description of the pre-chemical and chemical stage.
Keywords: oprava DNA; protony; DNA Damage; Kinetics; hydroxylový radikál; DNA; Coumarins; DNA Repair; proteiny z Escherichia coli; kumariny; poškození DNA; plazmidy; vztah dávky záření a odpovědi; Protons; Plasmids; kinetika; Hydroxyl Radical; Escherichia coli Proteins; Dose-Response Relationship, Radiation